Current outlook of ethics in research with human subjects - Takahashi,Marystella Tomoe (2011)
In the last decades, medical care has been increasingly permeated by the concept of evidence-based-medicine, in which clinical research plays a crucial role in establishing diagnostic and treatment. Following the improvements in clinical research, we have a growing concern and understanding that some ethical issues must be respected when the subjects are human beings. Research with human subjects relies on the principles of autonomy, beneficence, no maleficence and justice. Ordinance 196/96 from the National Health Board adds to the Brazilian legislation such renowned bioethical principles. AIM: Discuss the main ethical aspects involved in research with human subjects. MATERIALS AND METHODS: Critical analysis of Ordinance 196/96 and related literature. CONCLUSION: Ordinance 196/96 rules research with human subjects; nevertheless, it requires more in-depth discussions regarding the informed consent, use of placebo, research with vulnerable populations and research in developing countries.